Investigating Translators’ Work-related Happiness: Slovak Sworn and Institutional Translators as a Case in Point - Bednárová-Gibová, Klaudia; Madoš, Branislav (Meta, 2019)
This paper reports on an investigation which is part of a comprehensive project aimed at investigating translators’ work-related happiness in various contexts, a subject largely under-researched in contemporary translation studies. The purpose of this pilot cohort study is to determine the perceptions of happiness in two presumably high-profile groups of translators—Slovak sworn translators and Slovak EU translators. To accomplish the aim, comparative and causal perspectives are used. The quantitative analysis, comprising descriptive and correlation analysis, involves data from questionnaires completed by a total of 115 translators belonging to the two groups (83 + 32). The respondents’ perceptions of their work-related happiness are examined and compared, based on their responses to questions revolving primarily around social status variables and parameters of occupational prestige. Based on the gained data, seven hypotheses are tested with quantitative research methods employing contingency tables. Although our findings largely do not corroborate the hypotheses and lead to the identification of crucial differences between the two groups, the analyses also allow us to identify some commonalities. The results of the quantitative analysis are discussed in detail.